Rapidly progressive glomerulonephritis and acute kidney injury associated with cocaine use - Case report - Pimentel,Paulo Vitor de Souza (2021)
ABSTRACT A wide spectrum of renal complications can occur with acute and chronic use of cocaine. Most cases are related to rhabdomyolysis, but other mechanisms are malignant hypertension, renal ischemia, and rapidly progressive glomerulonephritis (RPGN) associated-ANCA vasculitis. In recent years, the use of cocaine adulterated with levamisole has been associated with ANCA vasculitis and pauci-immune RPGN. RPGN is clinically manifested as a nephritic syndrome with a rapid and progressive decline in renal function, and its histopathological finding is the presence of crescents in more than 50% of the glomeruli. We report a case of a 38-year-old man chronic user of cocaine, alcohol, and cigarettes who had red urine, oliguria, swollen legs and eyelids, as well as the uremic symptoms anorexia, emesis, and mental confusion. He was admitted with acute kidney injury and performed six hemodialysis sessions during the first 16 days of hospitalization and then was transferred to a tertiary hospital for diagnostic investigation. Tests of ANF (antinuclear factor), ANCA, anti-DNA, serology for hepatitis B, C, and HIV virus were negative. A renal percutaneous biopsy revealed crescentic glomerulonephritis with mild tubular atrophy. The patient underwent pulse therapy with methylprednisolone (for 3 days) and cyclophosphamide. Then he maintained daily prednisone and monthly intravenous cyclophosphamide and evolved with progressive improvement of renal function.